2021
DOI: 10.1093/jn/nxab145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency and its Sociodemographic Patterning in Indian Children and Adolescents: Findings from the Comprehensive National Nutrition Survey 2016–18

Abstract: Background Anemia control programs in India focus mainly on the measurement of hemoglobin in response to iron–folic acid supplementation. However, representative national estimates of iron deficiency (ID) are not available. Objectives The objective of the present study was to evaluate ID prevalence among children and adolescents (1–19 y) using nationally representative data and to examine the sociodemographic patterning of ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1,2 Potentially important causes for this are poor programmatic coverage and compliance to the iron folate (IFA) supplementation program, or persistent in ammation, or other causes. 3,4,5 It is worth considering whether the high anaemia prevalence is an in ated value, or whether iron or folate de ciency is not the primary aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Potentially important causes for this are poor programmatic coverage and compliance to the iron folate (IFA) supplementation program, or persistent in ammation, or other causes. 3,4,5 It is worth considering whether the high anaemia prevalence is an in ated value, or whether iron or folate de ciency is not the primary aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent national survey of iron status and anaemia reported that ID prevalence was higher, but anaemia was lower, in urban compared with rural children, pointing to a better iron utilisation for erythropoiesis in the former. 6 The findings here emphasise the greater importance of ensuring the supply of diverse food like the MDM single-nutrient supplementary approaches.…”
Section: Resultsmentioning
confidence: 76%
“…The prevalence of anaemia was reported by 58 studies across Afghanistan, Bangladesh, Bhutan, India, Nepal, Pakistan and Sri Lanka (Supporting Information: Table S5 ). Nationally representative data from Bangladesh, Sri Lanka and India indicated iron deficiency prevalence estimates of 7.1%, 19.2% and 30.0%, respectively (Kulkarni et al, 2021 ; Rahman et al, 2016 ; Wray et al, 2017 ). The prevalence of micronutrient deficiency reported by all studies (whether nationally representative or not) ranged from 1.8% (Pakistan, year undisclosed) (Zareen, 2021 ) to 87% (India in 2014–2015) (Ahankari et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%